2015
DOI: 10.1523/jneurosci.0193-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Hyperexcitability in CA3 Pyramidal Neurons Is Mediated by Enhanced A-Type K+Channel Function and Expression

Abstract: Aging-related impairments in hippocampus-dependent cognition have been attributed to maladaptive changes in the functional properties of pyramidal neurons within the hippocampal subregions. Much evidence has come from work on CA1 pyramidal neurons, with CA3 pyramidal neurons receiving comparatively less attention despite its age-related hyperactivation being postulated to interfere with spatial processing in the hippocampal circuit. Here, we use whole-cell current-clamp to demonstrate that aged rat (29 -32 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 56 publications
10
89
1
Order By: Relevance
“…Alterations in intrinsic excitability have been suggested to contribute to learning and memory (Zhang and Linden, 2003), age-related changes in neural function (Simkin et al, 2015), and a number of neuropsychiatric disorders, including autism (Cellot et al, 2016). Thus, the pronounced proximodistal gradient in intrinsic excitability in CA3 may contribute to the proximodistal gradient of CA3 place field properties (Lee et al, 2015; Lu et al, 2015) and memory encoding (Hunsaker et al, 2008) and should be incorporated into future computational models of the CA3 network.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in intrinsic excitability have been suggested to contribute to learning and memory (Zhang and Linden, 2003), age-related changes in neural function (Simkin et al, 2015), and a number of neuropsychiatric disorders, including autism (Cellot et al, 2016). Thus, the pronounced proximodistal gradient in intrinsic excitability in CA3 may contribute to the proximodistal gradient of CA3 place field properties (Lee et al, 2015; Lu et al, 2015) and memory encoding (Hunsaker et al, 2008) and should be incorporated into future computational models of the CA3 network.…”
Section: Discussionmentioning
confidence: 99%
“…Aging itself can be associated with limited memory impairment not only in elderly humans but also in many other species that do not develop Alzheimer’s disease (AD). Memory impairment in aged laboratory animals, including both rodents and non-human primates, is associated with increased neural activity in specific circuits within the hippocampal memory system (Thomé et al, 2016; Wilson et al, 2005; Simkin et al, 2015). Mounting evidence from basic science and clinical studies has also demonstrated that neuronal circuits become hyperactive particularly in early stages of AD (Busche et al, 2012; Busche and Konnerth, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The peak-to-trough ratio did not, however, vary significantly as a function of age (F (1,751) ϭ 3.52, p ϭ 0.06), nor was there a significant interaction effect between cell type and age (F (1,751) ϭ 0.97, p ϭ 0.32). This indicates that for both cell-type classifications, young and aged rats had similar peak-to-trough ratios, which is distinct from what has been reported for cells in CA1 (Landfield and Pitler, 1984;Pitler and Landfield, 1990;Landfield, 1996) and CA3 of the hippocampus (Simkin et al, 2015).…”
Section: Waveform Characteristics Of Principal Cells and Interneuronsmentioning
confidence: 43%